STUDY OF RAMAN SCATTERING AND HALLEFFECT FOR THE MgxZnO1-x /n-Si PHOTODETECTOR - Saleem H. Trier (Al-Qadisiyah Journal of Pure Science, 2019)
:  In this work MgxZnO1-x thin films have been prepared using a chemical spraying pyrolysis (CSP) technique , Mixed solutions MgxZnO1-x have been growth at different volumetric percentages (0, 30, 50, 70, and 90)% and deposited on silicon substrates  at temperatures (400,450, and 500) oC . The crystal structure was examined by using X-ray diffraction (XRD) technique. The results showed that all the films  prepared were polycrystalline, showing improvement in the crystal structure by change at temperature. Topography of the surface of the prepared films have been studied by using field emission scanning electron microscopy (FESEM), and energy dispersive X-ray spectroscopy (EDX).  It  showed that films contain elements (Si, N, O, Zn, and  Mg) as expected. Raman scattering have been measured for MgxZnO1-x/n-Si thin films at different Mg-content. It exhibits two  intense bands at (468 and 872) cm-1, corresponding to the second-order Raman scattering modes, and second-order mode the A1(LO) , is the first-order mode of ZnO. As it increases Mg-content up to (50)%, the A1(LO) mode the locate in intensity. The Hall effect have been studied,  results showed measurements Hall that the pure ZnO film was negative type (n-type), while MgxZnO1-x films were (p-type).